Kajian Teoritis Pembuatan Instalasi Elektrohidrolik Menggunakan Metode Cascade pada Mesin Kupas Serabut Kelapa - Hatuwe, Azmain Noor (Journal Mechanical Engineering, 2024)
The Department of Mechanical Engineering, Ambon State Polytechnic has made a machine for peeling coconut fiber. This machine has 4 pry blades which function, when stuck in the coconut fiber, they will make opposite movements, so they can tear the coconut fiber. In the operating process, this machine still uses human power, of course human power has limitations when peeling coconut fiber on a large scale. Therefore, the coconut peeling machine needs to be driven automatically using hydraulic power so that the work process does not depend on human power. The method used in this research is a theoretical study, where data obtained from the field is processed using references and devices that support the construction of electrohydraulic installations. Fluidsim software is needed to test the movement of electrohydraulic installations according to short notation A+ B+ B- A-. The working mechanism of an electrohydraulic installation in controlling the movement of a hydraulic cylinder is shown step by step in the form of a hydraulic diagram and an electro diagram.From the test results, information was obtained that the coconut peeling machine uses 2 cylinders as the driving force for the mechanical system of coconut fiber peeling knives. Working principle of electrohydraulic installation according to the cascade method, in the signal control installation section; relays k1 and k2 turn on alternately in sequence, and in the power control installation section, the relay switch will turn on the solenoids y1, y2, y3 and y4 sequentially according to the short notation. Keywords: Electrohydraulics, Cascade Method, Coconut Fiber Peeling Machine